2011
DOI: 10.4236/wjv.2011.14014
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Containing T-Cell Epitopes of <i>Chlamydia trachomatis</i> Recombinant MOMP Induces Systemic and Mucosal Antibody Responses in Mice

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recombinant MOMP-278 (M278) was cloned as previously reported 15 and encapsulated in PLA-PEG nanoparticles using a modified water/oil/water double emulsion evaporation technique 16,17 and then lyophilized in the presence of 5% trehalose (as a stabilizer) to obtain encapsulated-M278 (PLA-PEG-M278). Phosphate buffered saline (PBS) was similarly encapsulated in PLA-PEG to serve as a negative control (PLA-PEG-PBS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant MOMP-278 (M278) was cloned as previously reported 15 and encapsulated in PLA-PEG nanoparticles using a modified water/oil/water double emulsion evaporation technique 16,17 and then lyophilized in the presence of 5% trehalose (as a stabilizer) to obtain encapsulated-M278 (PLA-PEG-M278). Phosphate buffered saline (PBS) was similarly encapsulated in PLA-PEG to serve as a negative control (PLA-PEG-PBS).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we employed PLA-PEG as a delivery system for M278 15 , a C. trachomatis recombinant MOMP peptide, and hypothesized that encapsulation of M278 will provide for its sustained slow release to potentiate and bolster immune responses in mice. First, by in vitro studies we determined the physiochemical characteristics of encapsulated-M278 (size, zeta potential, morphology, absorbance and chemical compositions), encapsulation efficiency, release pattern, and toxicity to macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…IgG2a . IgG1, Taha et al [29] proposed that rMOMP-278 immunization induced a mixed Th1/Th2 response, but with a bias to Th1 response, in contrast to that rMOMP predominantly induced Th2 response with the order of specific antibody production of IgG1 . IgG2b .…”
Section: Discussionmentioning
confidence: 99%
“…Safety concerns have led to other strategies for vaccine development that focus on epitope vaccines. Taha et al [29] selected a small gene fragment from MOMP containing T-cell epitopes (aa 278-370) and generated a recombinant MOMP peptide (rMOMP-278, 93 aa). They used rMOMP-278 to immunize mice and found that the rMOMP-278 induced higher responses for antigen-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Sera collected two weeks following the last immunization from the groups of mice were pooled and used to detect anti-rMOMPspecific antibody responses as previously described, 35,49 except that 5 µg/mL of purified rMOMP was used to coat plates in the present study. To determine antibody concentrations (titers), two-fold serial dilutions of serum were made and added to appropriate wells, followed by addition of either horseradish peroxidase-conjugated goat antimouse immunoglobulin (Ig) G, Ig2a, or IgG1 (Southern Biotech, Birmingham, AL, USA) antibody at a dilution of1:2000.…”
Section: Antibody Determinationmentioning
confidence: 99%